2011
DOI: 10.1007/s10750-011-0824-z
|View full text |Cite
|
Sign up to set email alerts
|

Calcium content of littoral Cladocera in three softwater lakes of the Canadian Shield

Abstract: Aqueous calcium (Ca) concentrations are declining in softwater lakes of the Canadian Shield largely because of decades of acid deposition and afforestation following timber harvesting. Populations of pelagic cladoceran taxa with high Ca requirements, especially Daphnia spp., are declining in response to reduced aqueous Ca availability. However, the Ca content, and thus the requirements of littoral cladoceran taxa are unknown; therefore, the potential vulnerability of this major component of lake ecosystems to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…and Chydorus spp. ; Jeziorski and Yan 2006;Shapiera et al 2011) were examined. More specifically, as laboratory analyses of Ca limitation within the Cladocera have largely been limited to daphniid species, daphniid changes over time were examined among the two species complexes (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…and Chydorus spp. ; Jeziorski and Yan 2006;Shapiera et al 2011) were examined. More specifically, as laboratory analyses of Ca limitation within the Cladocera have largely been limited to daphniid species, daphniid changes over time were examined among the two species complexes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the littoral cladoceran community remains a large, untapped resource for Ca decline studies. Despite large differences in Ca content among some common littoral taxa (Shapiera et al 2011), the Ca requirements of the majority of taxa found in softwater Shield lakes remain unknown, and continued laboratory and field determinations to identify other Ca-sensitive taxa will be valuable. In the meantime, attempts to tease apart the effects of Ca decline from those of acidification will benefit greatly from the adoption of a multi-proxy approach, in order to distinguish between acidified and naturally acidic low Ca lakes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of Daphnia (in 3 lakes) and Eubosmina (in 11 lakes) at very low relative abundances was likely more associated with the morphometry of the studied lakes (small and shallow) than with dystrophic conditions. However, low Daphnia percentages may have also been linked with very low calcium content in the water of the lakes, an environmental condition that is critical for the development of most species belonging to this genus (Jeziorski et al 2008;Shapiera et al 2011).…”
Section: Discussionmentioning
confidence: 99%